In Response to: 'Impact of Glycosylation on Effector Functions of Therapeutic IgG' (Pharmaceuticals 2010, 3, 146-157) - Andreas Nechansky; Iris Koller; Ralf Kircheis (MDPI AG, 2010)
To complete the review article by Abes and colleagues (Pharmaceuticals 2010, 3, 146-157) which provides a good overview on recently developed approaches for generation of glyco-modified antibodies and the impact of glyco-modification of antibodies on their effector functions, important information should be added, namely that - besides the Glycart and the Biowa approach to generate de-fucosylated antibodies - innovative, moss derived methods have been shown to generate glyco-modified antibodies with improved effector function profile.